Analysis of Dataflow Programs with Interval-limited Data-rates - Bhattacharyya, Shuvra S.; Teich, Jürgen (Journal of VLSI Signal Processing Systems for Signal, Image, and Video Technology, 2006)
In this paper, we consider the problem of analyzing dataflow programs with the property that actor production and consumption rates are not constant and fixed, but limited by intervals. Such interval ranges may result from uncertainty in the specification of an actor or as a design freedom of the model. Major questions such as consistencyand buffer memory requirementsfor single-processor scheduleswill be analyzed here for such specifications for the first time. Also, metamodeling formulations of interval limited dataflow are discussed, with special emphasis on the application to cyclo-static dataflow modeling. © 2006 Springer Science + Business Media, LLC.
UnivIS-Import:2015-03-09:Pub.2006.tech.IMMD.inform.analys
Keywords: Buffer memory analysis; Interval rates; Scheduling dataflow models of computation